OUTCOMES OF UNILATERAL HEMILAMINECTOMY IN THE TREATMENT OF INTRADURAL EXTRAMEDULLARY TUMORS (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the efficacy and safety of unilateral hemilaminectomy in the treatment of intradural extramedullary tumors, with particular emphasis on postoperative outcomes and preservation of spinal stability.Methods: A retrospective study was conducted on 14 patients who underwent unilateral hemilaminectomy for resection of intradural extramedullary tumors at Hospital 1A between June 2022 and December 2023. Data regarding patient characteristics, tumor location, surgical outcomes, and postoperative complications were collected and analyzed.Results: Among the 14 patients, there were 9 women (64.3%) and 5 men (35.7%), with a mean age of 52 years (32-73 years). Tumors were located predominantly in the thoracic spine (8 cases) and lumbar spine (6 cases). 10 patients underwent resection involving 2 laminae, while 4 patients required resection across 3 laminae. Gross total resection was achieved in 92.9% of cases. Complications included 1 case of cerebrospinal fluid leakage and 2 cases of mild postoperative infection, all of which were managed conservatively. No postoperative spinal instability was observed.Conclusion: Unilateral hemilaminectomy is a safe and effective approach for the management of intradural extramedullary tumors, allowing adequate tumor resection with minimal invasiveness while preserving spinal stability.
Keywords: Unilateral hemilaminectomy, intradural extramedullary tumor, minimally invasive surgery, spinal instability, spine tumor surgery.